Cryopreserved Placental Explants Increase Lifespan of Male Mice and Change Survival Features of Female Mice - Prokopyuk, Vladimir Yu.; Chub, Oleg V.; Shevchenko, Nadezhda A.; Falko, Oksana V.; Musatova, Irina B.; Lazurenko, Victoria V.; Tischenko, Aleksandra N.; Prokopyuk, Olga S. (Problems of Cryobiology and Cryomedicine, 2017)
According to the WHO data, to date the population lifespan is increasing worldwide due to infant mortality decrease, rather than the duration and life quality of elderly people. Most effective geroprotectors affect the immune and nervous systems, cell cycle, metabolism of carbohydrates, stimulate autophagy. Bioobjects of placental origin possess similar properties. The research aim was to study the effect of cryopreserved human placental explants on lifespan of BALB/c mice. Kaplan-Meier survival curves were analyzed and survival indices were calculated. The differences were determined using the Log-rank test. It has been shown that implantation of cryopreserved placental explants to experimental animals significantly increases the indices in male mice as follows: median of lifespan - by 17.6%; average life expectancy – by 18.1%; 90% survival rate – by 20.8%; maximum lifespan – by 17.9%. The administration of placental explants to female mice did not affect their lifespan, but reduced the probability of death in the reproductive period. Probl Cryobiol Cryomed 2017; 27(2): 143–150<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" /><br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />